Five insights from the Global Burden of Disease Study 2019 - GBD 2019 Viewpoint Collaborators (Elsevier, 2022)
This article was published in The Lancet [ © 2020 The Author(s). Published by Elsevier Ltd. This is an Open Access Article under the CC BY 4.0 license..] and the definite version is available at: https://doi.org/10.1016/S0140-6736(20)31404-5 The Journal's website is at: https://www.sciencedirect.com/science/article/abs/pii/S0140673620314045?via%3Dihub